Very High‐Frequency Oscillations in Mesial Temporal Lobe Epilepsy: Identifying the Epileptogenic Zone - Stéphane Jean; Yihai Dai; Yan Cui; Donghuo Deng; Zhe Qian; Panashe Tevin Tagu; Weitao Chen; Weihong Liu; Xiaoqiang Wei; Xinrong Fang; Shiwei Song (Annals of Clinical and Translational Neurology)
ABSTRACT Objective To investigate the reliability of very high‐frequency oscillations (VHFOs, 500–2000 Hz) as biomarkers in identifying the epileptogenic zone (EZ) in mesial temporal lobe epilepsy (MTLE) patients. Methods We reviewed 19 MTLE patients who underwent stereo‐electroencephalography‐guided radiofrequency thermocoagulation. Interictal and ictal VHFOs were captured in four regions of interest (ROIs): amygdalohippocampal complex (AHC), parahippocampal gyrus (PG), white matter, and lateral temporal lobe. We analyzed the occurrence of VHFOs per minute, per contact: (a) in each ROI; (b) during awake resting state, sleep, and seizure within the seizure onset zone (SOZ) and non‐SOZ contacts; (c) in the EZ, propagation zone (PZ), and non‐involved zone (NIZ). The percentage and ratio of thermocoagulated VHFOs contacts in seizure‐free (SF) and non‐seizure‐free (NSF) patients were also analyzed. Results At the last follow‐up (19.31 ± 6.36 months), 13 patients were SF and 6 were NSF. The VHFOs rate was significantly higher in the SOZ contacts during the ictal than interictal period compared to non‐SOZ contacts. Very‐fast ripples rate was more prevalent in the EZ than in the NIZ. VHFOs rate was higher in the AHC and PG compared to other regions. At a group level, SF patients had a higher percentage and ratio of thermocoagulated VHFOs contacts compared to NSF patients. At a patient level, some NSF patients had most of their VHFO‐generating tissues ablated, while some SF did not. Interpretation The presence and ablation of VHFO‐generating areas was associated with good surgical outcome at a group level. However, at a patient level, VHFOs may not be as reliable in identifying the EZ.